The Deuteronomic school: history, social setting, and literature - Person, Raymond F. (Studies in biblical literature, 2002)
Redaction criticism and Deuteronomic literature -- The Deuteronomic school in the Persian period -- Scribal schools in the ancient Near East -- The Deuteronomic school in its oral world -- Deuteronomic literature during the time of Zerubbabel -- Deuteronomic literature after the time of Zerubbabel -- The Deuteronomic school and other postexilic literature